Cardiac Autonomic Effects of Secondhand Exposure to Nicotine from Electronic Cigarettes: An Exploratory Study. Issue 1 (February 2019) - Lee, Mi-Sun; Rees, Vaughan W.; Koutrakis, Petros; Wolfson, Jack M.; Son, Youn-Suk; Lawrence, Joy; Christiani, David C.
Abstract : Background: The rapid increase in prevalence of e-cigarette (EC) use may lead to widespread exposure to secondhand emissions among nonsmokers, but evidence on the potential cardiovascular health risks is limited. We aimed to investigate the effect of short-term secondhand exposure to nicotine from e-cigarette (EC) emissions on cardiac autonomic function using heart rate variability (HRV). Methods: A randomized, repeated measures crossover study of healthy nonsmoking volunteers was conducted. Standard deviation of NN intervals (SDNN), average of the standard deviation of NN intervals (ASDNN), root mean square of successive differences (rMSSD), and heart rate–corrected QT interval (QTc) were calculated during 1 hour of EC exposure session. Results: Nicotine from EC emissions was associated with a 7.8% decrease in SDNN (95% CI [confidence interval]: −11.2%, −4.3%), 7.7% decrease in ASDNN (95% CI: −11.0%, −4.2%), and 3.8 milliseconds decrease in QTc (95% CI: −5.8, −1.9). Compared with a short exposure time period (<15 minutes), greater nicotine associated with reductions in ASDNN ( P for interaction = 0.076) with longer exposure time periods. For QTc, greater nicotine associated with reductions were found during 15- to 30-minute exposure time period ( P for interaction = 0.04). Conclusion: We present the first evidence of cardiac autonomic effects of short-term secondhand exposure to nicotine from EC emissions among healthy nonsmokers. Further comprehensive research on EC exposure extending to more subjects and flavor compounds is warranted. Abstract : Supplemental Digital Content is available in the text.